On Fuzzy Fixed Points for Fuzzy Maps with Generalized Weak Property - Marwan Amin Kutbi; Jamshaid Ahmad; Akbar Azam; Nawab Hussain (Journal of Applied Mathematics)
Let (X,d) be a complex valued metric space and let S,T be mappings from X to a set of all fuzzy subsets of X. We present sufficient conditions for the existence of a common α-fuzzy fixed point of S and T. Our results improve and extend certain recent results in literature. Moreover, we discuss an illustrative example to highlight the realized improvements.